Formulasi dan Evaluasi Sediaan Tablet Parasetamol dengan Pati Umbi Porang (Amorphophallus muelleri Blume) Sebagai Bahan Pengisi - Hotma sarito Panjaitan; Roy Indrianto Bangar; Erida Novriani (Herbal Medicine Journal, 2026)
Paracetamol is a widely used analgesic–antipyretic drug; however, it exhibits poor flowability and compactibility, requiring suitable excipients in tablet formulation. This study aimed to formulate paracetamol tablets using porang tuber starch (Amorphophallus muelleri) as a filler and to evaluate the effect of its concentration on the physical properties of granules and tablets. Tablets were prepared by the wet granulation method using three concentrations of porang tuber starch: 10 mg (F1), 15 mg (F2), and 20 mg (F3). Granule evaluation showed moisture content ranging from 2.1–3.4%, flow time of 4.8–6.2 seconds, angle of repose of 25.6–30.4°, and compressibility index of 11.2–15.6%, indicating good flow and compressibility properties. Tablet evaluation demonstrated acceptable weight uniformity with deviations < 5%, hardness values of 5.1–7.8 kg, friability of 0.32–0.78%, and disintegration times of 3.4–6.8 minutes. The formulation containing 20 mg of porang tuber starch (F3) exhibited the most optimal characteristics, with the highest tablet hardness (7.8 kg) and the lowest friability (0.32%), while maintaining disintegration time within pharmacopeial limits. Therefore, porang tuber starch shows strong potential as a natural filler in paracetamol tablet formulations.